2013
DOI: 10.1007/s13277-013-1194-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HAX-1 in human colorectal cancer and its clinical significance

Abstract: Colorectal cancer (CRC) remains one of the most common cancers worldwide. HS1-associated protein X-1 (HAX-1) has been highlighted as an important marker in many types of cancers. However, little is known about the role of HAX-1 in CRC. The aim of this study was to analyze the correlation of HAX-1 expression with the clinicopathological features of CRC. The protein and mRNA levels of HAX-1 were examined by immunohistochemistry (IHC) and real-time quantitative reverse-transcriptase polymerase chain reaction (RT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…This finding was consistent with previous reports from other tumors [12][13][14][15]. We found that compared with adjacent non-tumor tissues the strong positive rate of HAX-1 were significantly higher in laryngeal carcinoma samples.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding was consistent with previous reports from other tumors [12][13][14][15]. We found that compared with adjacent non-tumor tissues the strong positive rate of HAX-1 were significantly higher in laryngeal carcinoma samples.…”
Section: Discussionsupporting
confidence: 93%
“…A final immunoreactivity score (IRS) was obtained for each case by multiplying the percentage and the intensity score. Protein expression levels were further analyzed by classifying IRS values as low (based on an IRS value lower than 4.5 which was the median of IRS values) and as high (based on an IRS value greater than 4.5 which was the median of IRS values) [13]. Ethics approval to perform this study was obtained from the Human Research Ethics Committee of the Affiliated Hospital of Nantong University, Jiangsu Province, China.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has also been observed that the homozygous mutations in Hax-1 gene or loss of Hax-1 are associated with severe congenital neutropenia and neurodevelopmental disorders. In addition, overexpression of Hax-1 has been observed in tissues from esophageal, lung and colon cancers [13, 14, 17, 20]. More significantly, in colorectal cancer the increased expression of Hax-1 correlates with the lymph node metastasis and poor prognosis of the patients[13].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies from several laboratories including ours have clearly established a crucial role for Hax-1 in cancer cell migration [5, 10-12]. More recently it has been shown that Hax-1 is overexpressed in many cancers and the increased expression of Hax-1 can be correlated with aggressive cancer metastasis[13-20]. Collectively these studies point to a novel, but yet to be resolved role for Hax-1 in tumor cell migration and metastasis.…”
Section: Introductionmentioning
confidence: 99%